Pelayanan International Tourism Di Kabupaten Banyuwangi Melalui Program Kursus Bahasa Asing Berbasis Desa - Moh. Mahmud; Maskur Maskur (IAI Darussalam, 2019)
The Foreign Language Course program based on the village is a government program in Banyuwangi Regency with budgeting from the APBD for a minimum of 3 months each year. The activity was carried out in order to equip community members regarding foreign language skills as a provision in increasing service to foreign tourists who came from various parts of the world to the Banyuwangi Regency. This study uses a qualitative approach in which researchers go directly and interact directly within the tourism community and foreign language courses to explore data and information related to the activity program. The findings in the field that the Banyuwangi Regency government in order to enhance the community in communication skills in terms of foreign languages, the Government has carried out The Foreign Language Course program based on village conducted in all villages in Banyuwangi with a budget from the Regional Budget.